Effect of gluing garment materials with adhesive inserts on their multidirectional drape and bending rigidity - Stępień Michał; Frydrych Iwona; Miśkiewicz Pamela (AUTEX Research Journal)
The article concerns the study on multidirectional drape and bending rigidity of six wool (clothing) fabrics with two types of adhesive inserts. The aim of research was to investigate the effect of joining woolen fabrics with “Freudenberg Vilene” adhesive inserts on the bending rigidity and multidirectional drape. The adhesive inserts were differentiated according to mass per square meter, while the fabrics were differentiated according to thickness, weave, and mass per square meter. Based on the scientific literature, the issues related to the methods of testing the bending rigidity and multidirectional drape coefficient were discussed. All the conducted tests were aimed at the proper selection of adhesive inserts for the designed clothing products. The use of adhesive inserts affects the bending stiffness and multidirectional drapeability of clothing material. The fabric weave significantly affects the values of bending rigidity and drapeability. As the thickness of adhesive inserts increases, the overall bending rigidity increases. The greater the fabric mass per square meter, the stiffer the fabric. As the mass per square meter and thickness increase, the multidirectional rigidity of fabrics increases. The value of bending rigidity for the plain fabric is higher compared to twill fabric.